Hybrid of carbon-supported Pt nanoparticles and three dimensional graphene aerogel as high stable electrocatalyst for methanol electrooxidation. (20th January 2016) - Zhao, Lei; Wang, Zhen-Bo; Li, Jia-Long; Zhang, Jing-Jia; Sui, Xu-Lei; Zhang, Li-Mei
Graphical abstract: Three-dimensional structured Pt/C/graphene aerogel hybrids demonstrate high stability towards methanol electrooxidation due to the unique 3D graphene structure as well as the efficient assembly between the Pt/C and graphene aerogel. Highlights: Pt/C/graphene aerogel (GA) hybrid catalyst synthesized via a facile hydrothermal process. Pt/C/GA possesses a well-defined 3D graphene framework with encapsulating of Pt/C catalyst. Pt/C/GA catalyst exhibits remarkably higher stability than standard Pt/C catalyst. This simple method can be widely applied in fabrication of high durable supported catalysts. Abstract: Three-dimensional (3D) structured Pt/C/graphene aerogel (Pt/C/GA) hybrid as a remarkable high stability electrocatalyst is synthesized through a facile and green hydrothermal process. Thanks to the unique 3D graphene framework structure, Pt/C/GA hybrid catalyst demonstrated enhanced stability towards methanol electrooxidation with no decrease of electrocatalytic activity. Besides, Pt/C/GA hybrid catalyst also exhibits a significantly enhanced stability to scavenge crossover methanol under the high potential in acid solution compared with the standard Pt/C catalyst: Pt/C catalyst lost nearly 40% of its initial activity after 1000 cyclic voltammetry cycles, by contrast, only 16% for Pt/C/GA. Moreover, it is noteworthy that after 200 cycles, the mass activity of Pt/C/GA is always much higher than that of Pt/C. A significant stability enhancement is achieved due to the unique 3D macroporous graphene structure as well as the efficient assembly between the Pt/C catalyst and graphene aerogel. Importantly, our synthetic strategy can be easily applied to the commercial PtRu/C catalyst to improve its durability. This simple, convenient and green synthetic method highlights the potential in fabrication of high durable electrocatalyst for fuel cell applications.